The President's 1978 National Urban Policy Report : A Biennial Report to the Congress Submitted Pursuant to Sections 702 and 703(a), National Urban Policy and New Communities Development Act, as Amended in 1977 - Department of Housing and Urban Development, Washington, DC. (Washington, D.C. : Distributed by ERIC Clearinghouse, 1978)
This report describes the process of drawing up a national urban policy, summarizes the views presented at various forums, and sketches much of the data and analyses relied upon by urban policymakers. Part I summarizes the process of American urbanization leading to the emergence of a new stage in urban development. Part II describes changing population trends and economic activity and its impact on the economic and social well being of urban communities. Part III discusses underlying changes in energy and resource availability, population, lifestyles, and the economy affecting urban and regional development. Part IV focuses attention on the problems of communities in economic transition. Part V summarizes the efforts and impacts of government at all levels and of the private sector in addressing urban needs. Part VI describes the process followed in developing national urban policy and summarizes the urban policy principles, objectives, and strategies recommended to the President. Transcripts of the National Urban Policy and New Community Development Act of 1970 and the President's Message to Congress on the National Urban Policy (1978), and a bibliography of sources are appended. (Author/MK)
Microfiche.
Keywords: Federal Government; Policy Formation; Public Policy; Urban Areas; Urban Demography; Urban Environment; Urban Improvement; Urban Planning; Urban Problems; Urbanization; Reports, Descriptive; Numerical/Quantitative Data